Systems Modeling of the Role of Interleukin-21 in the Maintenance of Effector CD4(+) T Cell Responses during Chronic Helicobacter pylori Infection - Carbo, Adria (American Society of Microbiology, 2014)
The development of gastritis during Helicobacter pylori infection is dependent on an activated adaptive immune response orchestrated by T helper (Th) cells. However, the relative contributions of the Th1 and Th17 subsets to gastritis and control of infection are still under investigation. To investigate the role of interleukin-21 (IL-21) in the gastric mucosa during H. pylori infection, we combined mathematical modeling of CD4(+) T cell differentiation with in vivo mechanistic studies. We infected IL-21-deficient and wild-type mice with H. pylori strain SS1 and assessed colonization, gastric inflammation, cellular infiltration, and cytokine profiles. Chronically H. pylori-infected IL-21-deficient mice had higher H. pylori colonization, significantly less gastritis, and reduced expression of proinflammatory cytokines and chemokines compared to these parameters in infected wild-type littermates. These in vivo data were used to calibrate an H. pylori infection-dependent, CD4(+) T cell-specific computational model, which then described the mechanism by which IL-21 activates the production of interferon gamma (IFN-γ) and IL-17 during chronic H. pylori infection. The model predicted activated expression of T-bet and RORγt and the phosphorylation of STAT3 and STAT1 and suggested a potential role of IL-21 in the modulation of IL-10. Driven by our modeling-derived predictions, we found reduced levels of CD4(+) splenocyte-specific tbx21 and rorc expression, reduced phosphorylation of STAT1 and STAT3, and an increase in CD4(+) T cell-specific IL-10 expression in H. pylori-infected IL-21-deficient mice. Our results indicate that IL-21 regulates Th1 and Th17 effector responses during chronic H. pylori infection in a STAT1- and STAT3-dependent manner, therefore playing a major role controlling H. pylori infection and gastritis.